An Analysis of Femicide on Online Media Reporting in Indonesia from the Perspective of Human Security - Ika Dewi Sartika Saimima; Endang Hadrian; Anggreany Haryani Putri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This article aims to explore theoretical problems related to femicide reporting that occurs in online media. There are two ways of thinking about femicides from a human security perspective; this is a form of continuous violence against women in the public sphere. Femicide that occurs in online media is an act of reporting that is carried out to gain readers without victims or their families. The next is Femicide in the sense of gender inequality in handling cases in the private sphere related to violence against women in private, such as domestic violence. A descriptive analysis method with a literature study approach and legislation is used to obtain actual data related to femicide cases in Indonesian online media. A qualitative approach is also used to analyze issues of femicide from a human security perspective. Through the Draft Criminal Code, criminal law reform is urgently needed in handling cases of violence against women. The imposition of criminal sanctions stipulated in the Criminal Code is carried out by weighing criminal sanctions plus 1/3 (one third) for perpetrators who are within the family scope. Likewise, if the perpetrator of the crime comes from a party outside the family, the criminal sanction is added by 1/3 (one-third) of the primary offense. This criminal weighting is expected to have a deterrent effect on perpetrators of violence against women.